A Study on the Effects of Employees Work Relationship to Job Performance; Basis for Enhancement: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Conflict can arise in any setting, and the workplace is certainly no different. Disputesbetween employees or a direct disagreement between an employee and a business ownerare situations that can occur frequently. One of the biggest issues is how the two parties talkto each other or if they talk to each other at all. If there isn't an easy way for the two partiesto communicate with each other and make themselves heard, the conflict can escalate intosomething much worse. This can lead to poor company morale or the termination of a teammember.The results of this study showed that the majority agreed that maintaining a goodenvironment is vital for every employee. The result shows that encouraging each employeeto feel open and comfortable in their work environment creates job satisfaction and socialinteraction that enables efficient work, various challenges employees face in the workplace,and various opportunities that foster healthy relationships between Employers andemployees to encourage their employers to improve an organization.The most valuable recommendation is the implementation and improvement of employeerelations and the careful and appreciative treatment of your employees.
Keywords: Business Administration